2018
DOI: 10.1136/bmjdrc-2018-000563
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pharmacological treatment of diabetes mellitus on dementia risk: systematic review and meta-analysis

Abstract: BackgroundThe association between diabetes mellitus (DM) treatment and dementia is not well understood.ObjectiveTo investigate the association between treatment of diabetes, hypoglycemia, and dementia risk.Research design and methodsWe performed a systematic review and meta-analysis of pharmacological treatment of diabetes and incident or progressive cognitive impairment. We searched Ovid MEDLINE, Embase, Cochrane Central Registry of Controlled Trials, and PsychINFO from inception to 18 October 2017. We includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 53 publications
3
49
0
3
Order By: Relevance
“…The effect of different diabetic medications on cognition or dementia outcomes remains unclear as few studies have investigated this area. 99 However, one meta-analysis of cohort studies of diabetes reported that, cross sectionally, people with diabetes taking metformin had lower prevalence of cognitive impairment (three studies OR 0·6, 95% CI 0·4–0·8) and, longitudinally, reduced dementia incidence (six studies HR 0·8, 95% CI 0·4–0·9) compared with those taking other medications or no medication. 100 However another analysis did not find a protective effect of metformin for incident dementia (three studies, RR 1·1, 95% CI 0·5–2·4) with possible harm with insulin therapy (1·2, 1·1–1·4); but this did not account for severity of diabetes of those with type 2 diabetes on insulin.…”
Section: Specific Potentially Modifiable Risk Factors For Dementiamentioning
confidence: 99%
“…The effect of different diabetic medications on cognition or dementia outcomes remains unclear as few studies have investigated this area. 99 However, one meta-analysis of cohort studies of diabetes reported that, cross sectionally, people with diabetes taking metformin had lower prevalence of cognitive impairment (three studies OR 0·6, 95% CI 0·4–0·8) and, longitudinally, reduced dementia incidence (six studies HR 0·8, 95% CI 0·4–0·9) compared with those taking other medications or no medication. 100 However another analysis did not find a protective effect of metformin for incident dementia (three studies, RR 1·1, 95% CI 0·5–2·4) with possible harm with insulin therapy (1·2, 1·1–1·4); but this did not account for severity of diabetes of those with type 2 diabetes on insulin.…”
Section: Specific Potentially Modifiable Risk Factors For Dementiamentioning
confidence: 99%
“…With particular reference to hypoglycemia, the glycemic threshold that triggers symptoms of hypoglycemia is less functional in elderly individuals than in younger patients; consequently, the occurrence of a glycemic event may more easily lead to arrhythmias, angina, and falls in elderly patients. In particular, severe hypoglycemic episodes have been shown to be associated to a twofold increase in the incidence of dementia, as shown by recent systematic reviews and a meta-analysis of the impact of pharmacologic therapy for diabetes on dementia [22].…”
Section: Hypoglycemiamentioning
confidence: 97%
“…doi: https://doi.org/10.14341/DM10202 САХАРОСНИЖАЮЩИЕ ЛЕКАРСТВЕННЫЕ СРЕДСТВА И РИСК РАЗВИТИЯ КН/ДЕМЕНЦИИ МЕТААНАЛИЗ В метаанализ J.M. McMilan et al [57] были включены результаты 13 исследований (4рандомизированные клинические исследования и 9 -наблюдательные) с количеством участников от 634 до 145 928 (72% >1000 участников, 70% включенных больных были старше 65 лет), период наблюдения в исследованиях варьировал от 6 мес до 14,7 года (77% ->3 лет). Критерием включения исследований в метаанализ было наличие у участников СД2, ассоциированного с деменцией или умеренными КН.…”
Section: A R T I C L E I N P R E S Sunclassified
“…В связи с этим можно ожидать, что сахароснижающие препараты с высоким профилем безопасности в отношении гипогликемии имеют определенные преимущества, поскольку их использование не будет повышать риск развития и прогрессирования КН. В цитируемых выше исследованиях [57,58] терапия метформином, в том числе для интенсивного контроля гликемии, не сопровождается увеличением риска развития деменции, кроме того, длительное использование данного препарата сопровождается снижением темпов прогрессирования КН, то есть можно предполагать наличие у метформина церебропротективного эффекта. В своем метаанализе J.M.…”
Section: A R T I C L E I N P R E S Sunclassified